Relation between innovation and 4.0 industry in micro and small enterprises: Case study research in Durango - Figueroa González, Ernesto Geovani; Herrera-Reyes, Diana Zoraya; Tortolero-Portugal, Rosalío; Pérez Saldaña, Felicidad; Sotelo Asef, Jesús Guillermo (RAN - Revista Academia & Negocios, 2024)
Purpose: To analyze the correlation between the innovation variable and its four dimensions -market-oriented, process, goods or services, and human resources -and Industry 4.0 variable in micro and small enterprises (MYPES) in the municipality of Durango, Mexico. Methodology: The study employed a quantitative approach using Pearson correlation analysis. Data collection was conducted through a questionnaire administered to 448 directors of micro and small enterprises. Results: Empirical data is provided on how innovation relates to the adoption of advanced technologies in a vital sector for the local economy, potentially applicable in other similar environments, such as in other countries in Latin America. Originality: It identifies and quantifies the relationship between dimensions of innovation and Industry 4.0 in MYPES of Durango, Mexico. The research analyzes the correlation in a particular region, making it comparable with similar studies in other contexts, and highlights the importance of innovation for the competitiveness of MYPES in the Industry 4.0 era. Implications: This study results may be useful in the formulation of public policies and strategies.